Sandwich pairs in $p$-Laplacian problems - Perera, Kanishka; Schechter, Martin (Topological Methods in Nonlinear Analysis, 2007)
We solve boundaryvalue problems for the $p$-Laplacian using the notion of sandwichpairs.